2016
DOI: 10.3892/ijo.2016.3680
|View full text |Cite
|
Sign up to set email alerts
|

CSF1 is involved in breast cancer progression through inducing monocyte differentiation and homing

Abstract: Despite the great progress in breast cancer research and treatment, measures for efficient targeting of triple‑negative breast cancer (TNBC) are still lacking. The well‑established dependency of cancer cells on their microenvironment suggests that targeting the tumor niche might form a novel therapeutic approach. We identified the tumor‑associated macrophage (TAM) infiltration in breast cancer tissues by immunohistochemistry, and analyzed overall survival (OS). U937 co‑cultures with MDA‑MB‑231, MDA‑MB‑468 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Activated Treg cells also evade tumor immunity by inhibiting effector cells, such as CD4 + and CD8 + T cells [72]. In addition, tumor infiltrated M2 macrophages exhibit a tumorigenic effect by producing high levels of IL-10 and TGF-β1 [73]. NRP1 enhances Treg cells for tumor infiltration and promotes macrophage differentiation, as preparation for the activation of immune evasion responses [60,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated Treg cells also evade tumor immunity by inhibiting effector cells, such as CD4 + and CD8 + T cells [72]. In addition, tumor infiltrated M2 macrophages exhibit a tumorigenic effect by producing high levels of IL-10 and TGF-β1 [73]. NRP1 enhances Treg cells for tumor infiltration and promotes macrophage differentiation, as preparation for the activation of immune evasion responses [60,74].…”
Section: Discussionmentioning
confidence: 99%
“…CSF1, which regulates the macrophage lineage, has been found to increase the expression of macrophages and TAM, control the differentiation and function of M2 macrophages, and act as an angiogenesis switch [71,75,76]. According to a related study, the gene inhibition of CSF1 in breast cancer cells affects tumor formation in immunodeficient mice [73]. In addition, multiple tumor cell injections in the mouse liver metastasis models were found to increase the number of CD4+ CD25 + Treg cells and the expression of cytokines IL-10 and TGFβ-1 [77].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, macrophage colony-stimulating factor (M-CSF, encoded by Csf1) is an essential factor for the maturation of monocytes/macrophages. Ding et al demonstrated that the more aggressive human MDA-MB-231 and MDA-MB-468 breast cancer cell lines show a higher expression of M-CSF than MCF-7 cells with less invasive phenotype [52]. Moreover, it has been noted that the enhanced expression of Csf1 was correlated with a worse prognosis of overall survival in breast cancer [53] and with increased infiltration of TAMs in colorectal cancer [54].…”
Section: Discussionmentioning
confidence: 99%
“…Colony sti-mulating factor 1 (Csf1) is involved in cancer growth, survival, and metastasis. Blockade of CSF1/CSF1R reprograms TAMs to enhance antigen presentation, thus improving the therapeutic effects of immunotherapies (1,19,30,89).…”
Section: Cytokines Are Upregulated In Tumors and Lungs From Nrf2 Ko Micementioning
confidence: 99%